Postneonatal mortality of severely small for gestational age extremely low birth weight infants - Yasuka Kimoto; Katsuya Hirata; Masatoshi Nozaki; Narutaka Mochizuki; Shinya Hirano; Kazuko Wada (Pediatrics and Neonatology)
Background: Infants born with weights below the 10th percentile of the expected birth weight for gestational age, defined as small for gestational age (SGA), have an increased risk of neonatal mortality and prematurity-related complications. However, the relationship between SGA and postneonatal (28 days to <1 year) mortality among extremely low birth weight infants (ELBWIs) remains uncertain. Hence, this study aimed to investigate the association between birth weight percentiles and postneonatal mortality in ELBWIs. Methods: A cohort of ELBWIs with a gestational age greater than 23 weeks who were admitted to Osaka Women's and Children's Hospital between 2008 and 2019 were considered eligible. Infants with major congenital anomalies, those large for their gestational age, or those who died within 28 days of birth were excluded. Baseline characteristics and outcomes of the three groups of ELBWIs–severe SGA (sSGA; birth weight, <3rd percentile), moderate SGA (mSGA; birth weight, 3rd to <10th percentile), and appropriate for gestational age (AGA; birth weight, 10th to <90th percentile)–were compared. Logistic regression analysis was used to identify perinatal factors associated with postneonatal mortality in sSGA infants. Results: sSGA ELBWIs demonstrated higher incidence of meconium obstruction (25% vs. 8.3% vs. 7.6%, P < 0.001), cholestasis (21% vs. 4.2% vs. 9.7%, P < 0.003), and postneonatal mortality (7.3% vs. 0% vs. 0.7%, P < 0.004) than mSGA and AGA ELBWIs. In the logistic regression analysis, cholestasis (odds ratio, 30.1; 95% confidence interval, 2.98–304) and sepsis (odds ratio, 13.5; 95% confidence interval, 1.06–173) were significantly related to postneonatal mortality among ELBWIs with sSGA. The leading cause of postneonatal mortality in sSGA ELBWIs was liver failure (55.5%). Conclusion: sSGA ELBWIs exhibited a higher rate of postneonatal mortality compared to mSGA and AGA ELBWIs. Therefore, strategies aimed at preventing liver dysfunction in severely cholestatic ELBWIs with sSGA are necessary.